KONSEP PENDIDIKAN GENDER DI DALAM ISLAM - Hanafi, Jonari (Prodi PAI IAILM Suryalaya, 2019)
This study aims of the current research is to figure out 1) Gender concept in education presektif; 2) The interpretation of AlQur’an in Al-Hujurat sentence 13 towards interpretation of Al Azhar by Buya Hamka; 3) Gender concept in Islam view according to Al-Qur’an in Al-Hujurat sentence 13 towards interpretation of Al Azhar by Buya Hamka. The method used to collect the data was Content Analysis, because in this research has normatif characteristic and has relation with the content of the text, that is Interpretation from interpreters in interpre the holly sentence of Al-Hujurat sentence 13. The result of this study is 1) The interpretation of Al-Qur’an in Al-hujurat sentence 13 explain that human in Alloh SWT view are same, not being one faction who exeed another faction. People can not priding upon lineage, preeminate of estae, affronting to poor man. And Alloh SWT describe that its main is being in godly. 2) In this sentence is being some concept of gender equivalence, they are : a) Alloh SWT was exlamation to al of human without differences by gender, skin tone, or another, this shown that all of human in reality are same, not being more exeed from the other. b) People can not choose in order to born at certain nation. Hence, inappropriate human being pluming him or flatter others because tribe factor or nation. c) Alloh specify other parameter to measure degree of dignity of human being, that is fear. This fear rate determine dignity and Iowliness of someone. 3) as for its implication to education of islam, among others: a) Sentences reintepretation of Al Qur'An and of Hadits which is diffraction of gender conducted continue (point ofview of islam). b) Curriculum national payload eliminating dikotomis among woman and men, that way also local curriculum by being based on equivalence, balance and justice. Curriculum compiled as according to and requirement of tipologi area started from Playgroup education to the University. c) Enableness of woman clan in informal education sector like giving of facility learn to start in subdistrict level until to regency level which adapted with requirement of area.